Impurity / Danger! - Burge (Islamic law and society, 2010)
Abstract Several recent monographs and articles discussing ritual purity in Islam stress the independence of Islamic notions of ritual purity from neighbouring religious traditions and highlight the fact that impurity is considered less 'dangerous' in Islam. In this article, I examine the role of angels in connection with ritual purity and suggest that a number of ahādtth contest the conventional understanding of Islamic ritual law. Impurity, I argue, is much more dangerous than the fuqahāa and many contemporary scholars have suggested.